Policy Implementation of the Joint Community Movement Program to Overcome Dense Slums and Poor Areas in Tangerang Regency - Suliyanti, Heri; Irwandi, Irwandi; Ginanjar, Arif; Fadli, Yusuf; Sarofah, Riska (ARISTO, 2023)
The purpose of this study is to find out how the implementation of the GEBRAK PAKUMIS Program policy in Tangerang Regency. The theory used in this study is the Merillee S. Grindle theory which states that the implementation of a policy is determined by the degree of implementation ability of the policy. This study uses descriptive qualitative methods with data collection techniques: documents, observations, and interviews with program implementers and beneficiary communities. The results showed that the implementation of the Gebrak Pakumis program policy in Tangerang Regency showed that the community was more active in planning, and they could find out how to build a slum area. From the Content of Policy, there are problems in terms of resources, namely the lack of sufficient builder who has certification and the budget issued is still not sufficient. In terms of the Context of Policy or the policy environment, there are no significant problems and all have supported the implementation of the Gebrak Pakumis program policy.